Non-motor Parkinson's: integral to motor Parkinson's, yet often neglected - Todorova, Antoniya (BMJ Publishing Group, 2014)
Non-motor symptoms are a key component of Parkinson's disease, possibly representing a clinical biomarker of its premotor phase. The burden of non-motor symptoms can define a patient's health-related quality of life. Non-motor symptoms substantially increase the cost of care—requiring increased hospitalisation and treatment—and pose a major challenge to healthcare professionals. However, clinicians often regard non-motor symptoms and their management as peripheral to that of the motor symptoms. Here, we address the clinical issues and unmet needs of non-motor symptoms in Parkinson's disease.